Association Between Sociodemographic Factors, Working Experience And Training Status With Knowledge Level Towards Food And Personal Hygiene Among Food Handlers In Kuala Lumpur, Malaysia - Shalinawati R; Mohamed NA; Jamaluddin TZMT; Shahlan S (International Organization Of Scientific Research (IOSR), 2024)
Non-Indexed Publication